A companion to ancient philosophy - Sanday, Eric; Kirkland, Sean D. (Rereading ancient philosophy., 2018)
A Companion to Ancient Philosophy is a collection of essays on a broad range of themes and figures spanning the entire period extending from the Pre-Socratics to Plato, Aristotle, and the Hellenistic thinkers. Rather than offering synoptic and summary treatments of preestablished positions and themes, these essays engage with the ancient texts directly, focusing attention on concepts that emerge as urgent in the readings themselves and then clarifying those concepts interpretively. Indeed, this is a companion volume that takes a very serious and considered approach to its designated task-accompanying readers as they move through the most crucial passages of the infinitely rich and compelling texts of the ancients. Each essay provides a tutorial in close reading and careful interpretation. Because it offers foundational treatments of the most important works of ancient philosophy and because it, precisely by doing so, arrives at numerous original interpretive insights and suggests new directions for research in ancient philosophy, this volume should be of great value both to students just starting off reading the ancients and to established scholars still fascinated by philosophy's deepest abiding questions. -- Provided by publisher.